2021
DOI: 10.1021/acs.energyfuels.0c03501
|View full text |Cite
|
Sign up to set email alerts
|

Improved Methane Adsorption Model in Shale by Considering Variable Adsorbed Phase Density

Abstract: Numerous models have been used to describe the isotherm adsorption of supercritical methane in porous media. Many models assume that the adsorbed phase density does not change with pressure during the adsorption process. However, recent studies show that this assumption is unreasonable, and the resulting error is enormous. Therefore, we propose an improved isotherm adsorption model in shale that assumes that the adsorbed phase density keeps changing and that adsorbed phase volume remains constant during the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…The absolute adsorption represents the total amount of gas molecules in the sorbed state. Assuming that the average adsorbed phase density is ρ abs , the adsorbed phase volume is V abs , and the bulk gas density is ρ g , then the relationship between the excess adsorption amount n ex and the absolute adsorption amount n abs can be described as The differences between the surface excess adsorption and the absolute adsorption are presented at low pressure and are substantial in high pressure . The absolute adsorption capacity of methane in porous media can be obtained using various semi-empirical models, including the Langmuir model and its various variants, the Dubinin–Radushkevich (DR) model, the supercritical Dubinin–Radushkevich (SDR) model, the Ono–Kondo model, and the simplified local density (SLD) model. , Currently, commonly used are the Langmuir model and its variants and the SDR model. , By fitting the excess adsorption isotherm obtained in the experiment, a series of adsorption parameters, such as absolute adsorption capacity and adsorbed phase density, can be obtained …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute adsorption represents the total amount of gas molecules in the sorbed state. Assuming that the average adsorbed phase density is ρ abs , the adsorbed phase volume is V abs , and the bulk gas density is ρ g , then the relationship between the excess adsorption amount n ex and the absolute adsorption amount n abs can be described as The differences between the surface excess adsorption and the absolute adsorption are presented at low pressure and are substantial in high pressure . The absolute adsorption capacity of methane in porous media can be obtained using various semi-empirical models, including the Langmuir model and its various variants, the Dubinin–Radushkevich (DR) model, the supercritical Dubinin–Radushkevich (SDR) model, the Ono–Kondo model, and the simplified local density (SLD) model. , Currently, commonly used are the Langmuir model and its variants and the SDR model. , By fitting the excess adsorption isotherm obtained in the experiment, a series of adsorption parameters, such as absolute adsorption capacity and adsorbed phase density, can be obtained …”
Section: Introductionmentioning
confidence: 99%
“…20,40−45 By fitting the excess adsorption isotherm obtained in the experiment, a series of adsorption parameters, such as absolute adsorption capacity and adsorbed phase density, can be obtained. 46 With the rise of shale gas resources, there has been a lot of research on the supercritical adsorption mechanism of methane: Ross et al carried out shale methane adsorption isotherm experiments at different temperatures and found that, if the formation temperature is too high, the shale methane adsorption capacity will be greatly reduced, 47 and Chalmers et al believes that, as the reservoir pressure increases, the shale gas adsorption capacity gradually increases. 48 The organic matter content and maturity of shale will also affect the adsorption capacity of shale.…”
Section: Introductionmentioning
confidence: 99%
“…The second review by Zhang and Cheng is a mini review on the technical aspects of sample preparation and data analysis using small-angle neutron scattering (SANS) and ultrasmall-angle neutron scattering (USANS) for shale samples. The original research articles cover a wide spectrum of research on shale gas, including reservoir characteristics, ,,, reservoir modeling, ,,, exploration, equipment-related, ,, gas transport properties, ,,,, shale property characterization, , gas adsorption, ,, gas generation, produced water treatment, , methane conversion, etc.…”
Section: Shale Gasmentioning
confidence: 99%
“…47,48 For CO 2 , the van der Waals density is 1028 kg/m 3 at a critical temperature of 304.2 K and a critical pressure up to 7.4 MPa. 44−46 However, previous studies have suggested that the assumed values of the adsorbed-phase gas density are inappropriate due to the lack of physical justification and large resulting error, 48,49 especially for the gas adsorption phenomenon in small pores under high-pressure conditions. 10 Hu et al (2020) 16 applied microscopic pore properties to evaluate the CH 4 adsorption capacity of coal.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorbed-phase density is a crucial parameter for evaluation of gas storage capacity. The absorbed-phase density of supercritical CH 4 is frequently assumed to be 372 or 424 kg/m 3 , in which the 372 kg/m 3 value is obtained using the van der Waals equation under critical conditions (4.6 MPa and 190.56 K), and the 424 kg/m 3 value is the liquid CH 4 density at the boiling point (0.1 MPa and 112.15 K). , For CO 2 , the van der Waals density is 1028 kg/m 3 at a critical temperature of 304.2 K and a critical pressure up to 7.4 MPa. However, previous studies have suggested that the assumed values of the adsorbed-phase gas density are inappropriate due to the lack of physical justification and large resulting error, , especially for the gas adsorption phenomenon in small pores under high-pressure conditions . Hu et al (2020) applied microscopic pore properties to evaluate the CH 4 adsorption capacity of coal.…”
Section: Introductionmentioning
confidence: 99%